Method for producing mucin nanofiber and use thereof

The method of producing mucin nanofibers by electrospinning a raw material solution with a high mucin weight ratio and a water-soluble polymer at a pH above the isoelectric point of mucin addresses the issues of low mucin content and bead formation, resulting in improved nanofiber quality and manufacturing efficiency.

JP2025059575APending Publication Date: 2025-04-10UNIVERSITY OF FUKUI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023169735
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-29
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

Existing methods for producing mucin nanofibers result in low mucin weight ratios and the formation of beads, with poor maneuverability during manufacturing, particularly due to the need for high-temperature processing of water-insoluble polymers.

Method used

A method involving a raw material solution with a mucin weight ratio greater than 50% and a water-soluble polymer, where the pH is above the isoelectric point of mucin, is subjected to electrospinning to produce mucin nanofibers with improved properties.

Benefits of technology

This method enables the production of mucin nanofibers with a high mucin weight ratio, suppresses bead formation, and enhances manufacturing operability, resulting in improved performance and application potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025059575000003
    Figure 2025059575000003
  • Figure 2025059575000004
    Figure 2025059575000004
  • Figure 2025059575000001
    Figure 2025059575000001
Patent Text Reader

Abstract

To provide a method for producing a mucin nanofiber, which can produce a mucin nanofiber that has a high mucin weight ratio, suppresses bead formation, and improves operability during production, and use thereof.SOLUTION: A mucin nanofiber is obtained by subjecting a raw material solution to electro-spinning, the raw material solution containing mucin and a water-soluble polymer, the weight ratio of mucin to the total weight of the mucin and the water-soluble polymer being more than 50 wt.%, and the pH of the raw material solution being equal to or higher than an isoelectric point of mucin.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing mucin nanofibers and uses thereof. [Background technology]

[0002] Mucin is a glycoprotein expressed on the surface of mucosal tissues (e.g., eyes, nose, stomach, intestines, etc.) and has effects such as protection from bacteria and viruses, moisture retention, wound healing, and symbiosis with intestinal bacteria. Mucin nanofibers can be obtained by subjecting a solution containing mucin to electrospinning to turn the mucin into fibers. Since mucin nanofibers have the effects of mucin described above, they are expected to be used in medicines, cosmetics, culture substrates, bioplastics, etc.

[0003] Conventionally, a method for producing mucin nanofibers is known in which a mixture of mucin and a polymer is subjected to electrospinning to obtain mucin nanofibers. For example, Patent Document 1 discloses a method in which a mixture of mucin and a water-insoluble or poorly water-soluble polymer such as polycaprolactone and a lactic acid-glycolic acid copolymer is subjected to electrospinning. On the other hand, Non-Patent Document 1 discloses a method in which a mixture of a small amount of mucin and a large amount of polyvinyl alcohol, which is a water-soluble polymer, is subjected to electrospinning. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] WO2017 / 179055 publication [Non-patent literature]

[0005] [Non-Patent Document 1] AW Nugroho et al., IJETER,2020,8,6,2431-2437 Summary of the Invention [Problem to be solved by the invention]

[0006] Mucin nanofibers produced using conventional technologies had room for improvement in that they had a low mucin weight ratio, which led to the formation of beads (in this specification, "beads" refers to the granular regions that can be seen on the nanofiber when the nanofiber is observed under a scanning electron microscope, as described below), and the operability during production was poor (for example, water-insoluble or poorly water-soluble polymers needed to be heated to high temperatures in an acidic or alkaline solution).

[0007] One aspect of the present invention is to provide a method for producing mucin nanofibers that can produce mucin nanofibers with a high weight ratio of mucin, suppressed bead formation, and improved operability during production, and uses of the same. [Means for solving the problem]

[0008] One aspect of the present invention includes the following configuration.

[0009] [1] A method for producing mucin nanofibers, comprising a fiber formation step of electrospinning a raw material solution containing mucin and a water-soluble polymer, wherein the ratio of the weight of the mucin to the total weight of the mucin and the water-soluble polymer is greater than 50% by weight and the pH of the raw material solution is equal to or higher than the isoelectric point of the mucin, to obtain mucin nanofibers.

[0010] [2] The method for producing mucin nanofibers described in [1], wherein the zeta potential of the raw material solution is negative.

[0011] [3] The method for producing mucin nanofibers described in [1] or [2], wherein the average particle diameter of particles derived from mucin molecules contained in the raw material solution is 300 nm or less.

[0012] [4] A method for producing mucin nanofibers described in any one of [1] to [3], wherein the water-soluble polymer is a water-soluble polymer having at least one selected from the group consisting of a hydroxyl group, an amino group, a carboxyl group, and an ether bond.

[0013] [5] The method for producing mucin nanofibers described in any one of [1] to [4], wherein the water-soluble polymer is polyethylene oxide, polyvinyl alcohol, polyvinylpyrrolidone, polyethylene glycol, polyethyleneimine, polyacrylic acid, hydroxypropyl methylcellulose, methylcellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, polycarbophil, alginic acid, chitosan, β-glucan, gelatin, collagen, a mixture thereof, a derivative thereof, or a copolymer thereof.

[0014] [6] A method for producing mucin nanofibers described in any one of [1] to [5], comprising at least one of a crosslinking step of crosslinking mucin contained in the mucin nanofibers obtained by the fiber formation step and / or crosslinking mucins contained in the raw material solution used in the fiber formation step, and a washing step of washing the mucin nanofibers obtained by the fiber formation step with an aqueous solvent.

[0015] [7] A mucin nanofiber comprising mucin and, optionally, a water-soluble polymer, The weight ratio of the mucin to the total weight of the mucin and the water-soluble polymer is more than 50% by weight and 100% by weight or less; The mucin nanofiber has a water-insoluble polymer content of 9% by weight or less relative to 100% by weight of the mucin nanofiber.

[0016] [8] The mucin nanofiber described in [7], wherein the mucin has been crosslinked and / or washed.

[0017] [9] An article comprising the mucin nanofiber described in [7] or [8].

[0018]

[10] The article according to [9], which is an in vitro evaluation device, a medicine, a quasi-drug, a cosmetic, a substrate, a collection material, a pharmaceutical DDS device, a cryopreservation device, an adhesive, an eye patch, a bandage, or a napkin. Effect of the Invention

[0019] According to one aspect of the present invention, it is possible to provide a method for producing mucin nanofibers that can produce mucin nanofibers with a high weight ratio of mucin, suppressed bead formation, and improved operability during production, and use of the same. [Brief description of the drawings]

[0020] [Figure 1] FIG. 1 is a graph showing the relationship between the pH of a purified mucin solution (0.1 w / v%) and the average particle size of particles derived from mucin molecules, and a graph showing the relationship between the pH of a purified mucin solution (0.1 w / v%) and the zeta potential of the raw material solution, according to one embodiment of the present invention. [Diagram 2] FIG. 2 is an electron micrograph of a spun mucin nanofiber according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] Hereinafter, the embodiments of the present invention will be described in detail. However, the present invention is not limited to this, and various modifications are possible within the scope described, and embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present invention. In addition, unless otherwise specified in this specification, "A to B" representing a numerical range means "A or more, B or less."

[0022] <1. Method for producing mucin nanofiber> A method for producing mucin nanofibers according to one embodiment of the present invention includes a fiber formation step of electrospinning a raw material solution containing mucin and a water-soluble polymer, the ratio of the weight of the mucin to the total weight of the mucin and the water-soluble polymer being greater than 50% by weight, and the pH being equal to or higher than the isoelectric point of the mucin, to obtain mucin nanofibers. Hereinafter, the "method for producing mucin nanofibers according to one embodiment of the present invention" may be referred to as "this production method".

[0023] This manufacturing method makes it possible to produce mucin nanofibers that have a high mucin weight ratio, suppress the formation of beads, and improve operability during manufacturing. This can contribute to the achievement of the Sustainable Development Goals (SDGs), such as Goal 3 "Ensure healthy lives and promote well-being for all at all ages."

[0024] The mucin nanofiber obtained by this production method is also one embodiment of the present invention. In this specification, the "mucin nanofiber according to one embodiment of the present invention" may be referred to as the "mucin nanofiber".

[0025] [1-1] Mucin In this specification, "mucin" refers to a glycoprotein having a repeating sequence rich in glycans in the core protein. Mucins are classified into membrane-bound and free types, but the present production method can be applied to both membrane-bound and free types. Most free mucins contain more cysteine ​​than membrane-bound mucins. Free mucins can form bonds with other substances that have various effects via cysteine. From the viewpoint of expanding the applicability of the produced mucin nanofibers, the mucin used in the present production method is preferably free mucin.

[0026] The type of mucin is not particularly limited, but examples thereof include submandibular mucin, sublingual mucin, intestinal mucin, etc. The above mucins may be used alone or in combination of two or more kinds.

[0027] Examples of free mucins include MUC2, MUC5AC, MUC5B, MUC6, MUC7, MUC9, and MUC19. Examples of membrane-bound mucins include MUC1, MUC3, MUC4, MUC12, MUC13, MUC15, MUC16, MUC17, and MUC20.

[0028] The mucin may be derived from an animal or another organism. Examples of the animals and organisms include primates such as humans, monkeys, and chimpanzees; mammals such as cows, pigs, sheep, goats, horses, dogs, cats, rabbits, mice, and rats; fish such as eels, loaches, catfish, conger eels, pufferfish, and parrotfish; mollusks such as squids, turban shells, and snails; and marine organisms such as jellyfish.

[0029] In this specification, "mucin" may include not only mucin but also mucin-like substances. Therefore, the raw material solution may contain mucin (mucin and / or mucin-like substances). The mucin-like substances are glycoproteins derived from plants. Examples of the mucin-like substances include plant viscous components (e.g., mucilage, etc.) from okra, yam, mushrooms, etc.

[0030] Other substances that form bonds with mucin are not limited and may be appropriately selected depending on the desired function that the mucin nanofiber is to have. Examples of the other substances include antibiotics, antibacterial substances, anti-inflammatory substances, steroids, immunosuppressants, cell growth factors, cell scaffolding molecules, antiviral agents, enzyme inhibitors, metal chelating agents, bacterial colonization factors, and viral adhesion factors.

[0031] [1-2] Water-soluble polymers As used herein, the term "water-soluble polymer" refers to a polymer that is soluble in water. More specifically, as used herein, the term "water-soluble polymer" refers to a polymer that is soluble in water at room temperature (e.g., 25°C). Water-soluble polymers are advantageous in that they are easily dissolved in water and do not require the use of an acidic or alkaline solution and / or heating for dissolution.

[0032] In the present production method, the water-soluble polymer is preferably a water-soluble polymer having at least one selected from the group consisting of a hydroxyl group, an amino group, a carboxyl group, and an ether bond, which has the advantage that the mucin nanofiber can be produced more easily.

[0033] In the present production method, the water-soluble polymer is preferably at least one selected from polyethylene oxide, polyvinyl alcohol, polyvinylpyrrolidone, polyethylene glycol, polyethyleneimine, polyacrylic acid, hydroxypropylmethylcellulose, methylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, polycarbophil, alginic acid, chitosan, β-glucan, gelatin, collagen, mixtures thereof, derivatives thereof, or copolymers thereof. The water-soluble polymer may be used alone or in combination of two or more. The water-soluble polymer has the advantage that the mucin nanofiber can be produced more easily.

[0034] [1-3] Raw material solution As used herein, the term "raw material solution" refers to a mixed solution containing mucin and a water-soluble polymer.

[0035] In this production method, the weight ratio of mucin in the raw material solution is more than 50% by weight, preferably 60% by weight or more, more preferably 70% by weight or more, even more preferably 80% by weight or more, and particularly preferably 90% by weight or more, based on the total weight of mucin and water-soluble polymer. If the weight ratio of mucin is more than 50% by weight, the present mucin nanofibers (e.g., mucin nanofibers having a high weight ratio of mucin) can be produced. The upper limit of the weight ratio of mucin in the raw material solution can be, for example, less than 100% by weight, 95% by weight or less, or 90% by weight or less, based on the total weight of mucin and water-soluble polymer.

[0036] In this production method, the weight ratio of the water-soluble polymer in the raw material solution is less than 50% by weight, preferably 40% by weight or less, more preferably 30% by weight or less, even more preferably 20% by weight or less, and particularly preferably 10% by weight or less, based on the total weight of the mucin and the water-soluble polymer. If the amount of water-soluble polymer used is less than 50% by weight, the present mucin nanofiber (e.g., mucin nanofiber having a high weight ratio of mucin) can be produced. The lower limit of the weight ratio of the water-soluble polymer in the raw material solution can be, for example, more than 0% by weight, 5% by weight or more, or 10% by weight or more, based on the total weight of the mucin and the water-soluble polymer.

[0037] In this production method, the pH of the raw material solution is equal to or higher than the isoelectric point of mucin. The isoelectric point of mucin varies depending on the type of mucin used. Therefore, in this production method, the pH of the raw material solution can be, for example, 4.0 or higher, 4.5 or higher, 5.0 or higher, 6.0 or higher, 7.0 or higher, 8.0 or higher, 9.0 or higher, 10.0 or higher, or 11.0 or higher. In this production method, the upper limit of the pH of the raw material solution is not limited and can be, for example, 11.0 or 12.0. If the pH of the raw material solution is equal to or higher than the isoelectric point of mucin, the present mucin nanofiber can be produced.

[0038] In this manufacturing method, the zeta potential of the raw material solution is preferably negative. If the zeta potential of the raw material solution is negative, the mucin nanofiber can be manufactured more easily. In this manufacturing method, the zeta potential of the raw material solution can be, for example, less than 0 mV, -1.0 mV or less, -3.0 mV or less, -5.0 mV or less, -7.0 mV or less, -10.0 mV or less, -13.0 mV or less, -15.0 mV or less, -17.0 mV or less, or -20.0 mV or less. In this manufacturing method, the lower limit of the zeta potential of the raw material solution is not limited and can be, for example, -25.0 mV or -30.0 mV.

[0039] In the present production method, the average particle size of the particles derived from mucin molecules contained in the raw solution is preferably 300 nm or less, more preferably 250 nm or less, even more preferably 200 nm or less, even more preferably 150 nm or less, and particularly preferably 100 nm or less. The lower limit of the average particle size of the particles derived from mucin molecules contained in the raw solution is not limited and may be, for example, 0.01 nm, 0.1 nm, 5 nm, or 10 nm. If the average particle size of the particles derived from mucin molecules contained in the raw solution is within the above range, the present mucin nanofibers (e.g., mucin nanofibers in which bead formation is suppressed) can be produced more easily.

[0040] The raw material solution may further contain an aqueous solvent. The aqueous solvent may be water alone or may be a mixed solvent of water and a hydrophilic organic solvent compatible with water. In the mixed solvent, the concentration of the hydrophilic organic solvent is not particularly limited.

[0041] The hydrophilic organic solvent is not particularly limited, but examples thereof include alcohols such as methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, isobutanol, pentanol, hexanol, and heptanol; ketones such as acetone and methyl ethyl ketone; ethers such as tetrahydrofuran and dioxane; nitriles such as acetonitrile and propionitrile; amides such as dimethylformamide and acetamide; polyols such as glycerin, ethylene glycol, and propylene glycol; dimethyl sulfoxide, pyridine, piperidine, etc. Among them, methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, isobutanol, acetone, methyl ethyl ketone, tetrahydrofuran, dioxane, acetonitrile, propionitrile, glycerin, ethylene glycol, and propylene glycol are preferred because they are easy to remove. Moreover, methanol, ethanol, 1-propanol, 2-propanol, butanol, acetone, glycerin, ethylene glycol, propylene glycol, etc. are more preferable because they are easily available. Furthermore, methanol, ethanol, acetone, glycerin, ethylene glycol, and propylene glycol are particularly preferable.

[0042] The water content in the entire aqueous solvent that can constitute the raw material solution is not limited and may be, for example, 5 to 100% by weight, 10 to 100% by weight, 30 to 100% by weight, 50 to 100% by weight, 70 to 100% by weight, 90 to 100% by weight, or 95 to 100% by weight.

[0043] The concentrations of each of the mucin and the water-soluble polymer in the raw material solution are not limited and may be, for example, 1 to 60 (w / v%), 1 to 50 (w / v%), 1 to 40 (w / v%), 1 to 30 (w / v%), 1 to 20 (w / v%), 1 to 10 (w / v%), or 1 to 5 (w / v%).

[0044] From the viewpoint of improving the properties of the resulting mucin nanofibers, the raw material solution may contain substances other than mucin, water-soluble polymers, and aqueous solvents (other substances), such as crosslinkers, antioxidants, chelating agents, buffers, preservatives, surfactants, inorganic salts, polyphenols, metal ions, acids, bases, amino acids, peptides, proteins, sugars, nucleic acids, lipids, cells, bacteria, and viruses.

[0045] [1-4] Mucin nanofiber In this specification, "mucin nanofiber" refers to nanofibers containing mucin. In this specification, "nanofiber" refers to fibers with an average fiber diameter on the order of nanometers. The average fiber diameter is not limited, and may be, for example, 1 nm or more and less than 1000 nm, 10 nm or more and less than 1000 nm, 100 nm or more and less than 1000 nm, 200 nm or more and less than 1000 nm, 300 nm or more and less than 1000 nm, 400 nm or more and less than 1000 nm, 500 nm or more and less than 1000 nm, 600 nm or more and less than 1000 nm, 700 nm or more and less than 1000 nm, or 800 nm or more and less than 1000 nm. Details of mucin nanofibers will be described later in <2. Mucin nanofibers>.

[0046] [1-5] Fiber formation process This production method has a fiber formation step of electrospinning a raw material solution containing mucin and a water-soluble polymer, where the ratio of the weight of the mucin to the total weight of the mucin and the water-soluble polymer is more than 50% by weight and the pH is equal to or higher than the isoelectric point of mucin, to obtain mucin nanofibers. The inclusion of the fiber formation step in this production method has the advantage that it is possible to produce the mucin nanofibers and that changes in the fiber shape and structure of the mucin nanofibers can be suppressed in the washing step described below.

[0047] The present manufacturing method may include, prior to the fiber forming step, a raw material solution preparation step for preparing a raw material solution to be used in the fiber forming step.

[0048] (Preparation of raw material solution) The process for preparing the raw material solution is not particularly limited, but examples include a process for adding mucin to an aqueous solvent having a water-soluble polymer dispersed therein and stirring the same, a process for adding a water-soluble polymer to an aqueous solvent having a mucin dispersed therein and stirring the same, a process for adding powders of mucin and the water-soluble polymer to an aqueous solvent and stirring the same, and a process for mixing an aqueous solvent having a water-soluble polymer dispersed therein with an aqueous solvent having a mucin dispersed therein.

[0049] In this specification, "subjecting the raw material solution to electrospinning" means electrospinning (electrospinning). Electrospinning can be performed by a known method. For example, the raw material solution is filled into a syringe at a constant speed by a syringe pump, and the raw material solution is sprayed into a solvent from the nozzle of a nozzle attached to the tip of the syringe by a voltage (e.g., 25 kV), and the sprayed jet is wound up by a collector.

[0050] The viscosity, conductivity, elasticity, and surface tension of the raw material solution are not limited and can be appropriately set according to a known method. In electrospinning, the atmospheric temperature, humidity, and pressure are not limited and can be appropriately set according to a known method.

[0051] In electrospinning, the voltage is not particularly limited as long as it is a voltage at which a jet is ejected. The voltage may be, for example, 10 kV to 30 kV, 15 kV to 25 kV, or 25 kV. From the viewpoint of using a voltage according to the type of raw material solution and / or adjusting the average fiber diameter of the nanofibers, the voltage may be more than 30 kV, 40 kV or more, or 50 kV or more. The voltage may be a positive output or a negative output. A voltage amplifier may also be used.

[0052] In electrospinning, the amount of solution delivered, the distance between the nozzle and the collector, and the take-up speed by the collector are not limited, and can be set appropriately according to known methods.

[0053] The present production method preferably includes at least one of a crosslinking step of crosslinking mucin contained in the mucin nanofibers obtained in the fiber formation step, and a washing step of washing the mucin nanofibers obtained in the fiber formation step with an aqueous solvent. This configuration makes it possible to suitably produce the present mucin nanofibers (e.g., mucin nanofibers having a high weight ratio of mucin).

[0054] [1-6] Crosslinking process The present production method preferably includes a crosslinking step of crosslinking mucin contained in the mucin nanofibers obtained in the fiber formation step, or crosslinking mucins contained in the raw material solution used in the fiber formation step. By including a crosslinking step in the present production method, it is possible to (i) increase the strength of the mucin nanofibers, and (ii) prevent the mucin in the mucin nanofibers from dissolving in an aqueous solvent in the washing step described below, thereby making it possible to remove the water-soluble polymer in the mucin nanofibers, and thus suppress changes in the fiber shape and structure of the mucin nanofibers. This also has the advantage of making it possible to increase the mucin ratio in the mucin nanofibers.

[0055] The above-mentioned crosslinking step is not particularly limited, but examples include a step of mixing a crosslinking agent with the mucin nanofiber to cause a crosslinking reaction, a step of mixing a crosslinking agent with the mucin nanofiber and then heating the mixture as necessary to cause a crosslinking reaction, a step of mixing a crosslinking agent with uncrosslinked mucin before electrospinning to cause a crosslinking reaction, and a step of mixing a crosslinking agent with uncrosslinked mucin before electrospinning and then heating the mixture as necessary to cause a crosslinking reaction.

[0056] The crosslinking agent is not particularly limited, but for example, when a crosslinking agent is mixed with a mucin nanofiber, a surface crosslinking agent can be used, and when a crosslinking agent is mixed with uncrosslinked mucin prior to electrospinning, an internal crosslinking agent can be used.

[0057] As the surface crosslinking agent, an organic or inorganic surface crosslinking agent can be used, and specifically, one or more compounds disclosed in U.S. Patent No. 7,183,456 can be used. More specifically, the surface crosslinking agent includes polyhydric alcohol compounds, epoxy compounds, haloepoxy compounds, polyamine compounds or their condensates with haloepoxy compounds, oxazoline compounds, oxazolidinone compounds, polyvalent metal salts, alkylene carbonate compounds, cyclic urea compounds, and the like. One of these surface crosslinking agents may be used alone, or two or more may be used in combination. In addition, it is preferable to use these surface crosslinking agents in the state of an aqueous solution (i.e., in the state of a surface crosslinking liquid).

[0058] The amount of surface crosslinking agent used in the crosslinking step (total amount used when multiple agents are used) is, for example, 0.01 to 10 parts by mass, or 0.01 to 5 parts by mass, per 100 parts by mass of mucin nanofibers. The surface crosslinking agent may also be added to the mucin nanofibers in the form of an aqueous solution. In this case, the amount of the aqueous solution added is, for example, 0.1 to 20 parts by mass, or 0.5 to 10 parts by mass, per 100 parts by mass of mucin nanofibers. Furthermore, if necessary, the above-mentioned hydrophilic organic solvent may also be used in combination, and in that case, the amount of the hydrophilic organic solvent added is, for example, 10 parts by mass or less, or 5 parts by mass or less, per 100 parts by mass of mucin nanofibers. Of course, the present production method is not limited to these configurations.

[0059] Examples of the internal crosslinking agent include the compounds described in U.S. Patent No. 6,241,928. Taking reactivity into consideration, one or more of these compounds can be used as the internal crosslinking agent.

[0060] The amount of the internal crosslinking agent used (content in the raw solution) is, for example, 0.0001 mol % to 10 mol %, or 0.001 mol % to 1 mol %, relative to the total amount of mucin and water-soluble polymer. Note that the mol % relative to the total amount of mucin and water-soluble polymer refers to the percentage of the number of moles of the internal crosslinking agent relative to the total number of moles of mucin and water-soluble polymer contained in the raw solution.

[0061] The crosslinking step may include a mixing step (A) in which the mucin nanofibers and the crosslinking agent are mixed. The method for mixing the mucin nanofibers and the crosslinking agent in the mixing step (A) is not particularly limited, but examples include a method in which a solution containing the crosslinking agent is prepared in advance and the solution is preferably sprayed or dropped onto the mucin nanofibers, more preferably sprayed and mixed, and a method in which the mucin nanofibers and the crosslinking agent are placed in the same container and mixed by vapor diffusion of the crosslinking agent.

[0062] Devices for mixing mucin nanofibers with a crosslinking agent include, but are not limited to, high-speed stirring mixers, equipment used for crosslinking by vapor diffusion (e.g., equipment in which a glass petri dish containing mucin nanofibers before crosslinking and a solution containing a crosslinking agent is placed into a plastic container and sealed), and high-speed stirring continuous mixers.

[0063] The crosslinking step may include a mixing step (B) in which mucin (e.g., mucin contained in a raw material solution) is mixed with a crosslinking agent. The method for mixing mucin with a crosslinking agent in the mixing step (B) is not particularly limited, but examples include a method in which a solution containing a crosslinking agent is prepared in advance, and mucin is added to the solution and mixed.

[0064] (Heat treatment process) The crosslinking step may include a heat treatment step of heating the mixture obtained in the mixing step (A) to cause a crosslinking reaction on the surface of the mucin nanofibers. The crosslinking step may include a heat treatment step of heating the mixture obtained in the mixing step (B) to cause a crosslinking reaction between mucins.

[0065] The apparatus for carrying out the heat treatment is not particularly limited, but a paddle dryer is preferred. The heating temperature in the heat treatment, in other words, the reaction temperature in the crosslinking reaction, is appropriately set according to the type of crosslinking agent used, and is, for example, 25°C to 50°C, 25°C to 40°C or less, or 25°C to 30°C.

[0066] The heating time at the heating temperature is not particularly limited, but is, for example, 1 minute to 15 hours, or 1 hour to 10 hours, which allows the cross-linking reaction of mucin to proceed sufficiently.

[0067] (cooling process) The crosslinking step may include a cooling step of cooling the crosslinked mucin nanofibers or the mucin-mucin crosslinked complex after the heat treatment step.

[0068] The cooling device used in the cooling step is not particularly limited, but is preferably a device with the same specifications as the device used in the heat treatment step, and more preferably a paddle dryer. This is because it can be used as a cooling device by changing the heat medium to a refrigerant. Note that the crosslinked mucin nanofibers or the complex of crosslinked mucin and mucin obtained in the heat treatment step are forcibly cooled, as necessary, in the cooling step to, for example, 40°C or higher and 80°C or lower, or 50°C or higher and 70°C or lower.

[0069] (drying process) The crosslinking step may include a drying step in which, after completion of the crosslinking reaction, the aqueous solvent is removed from the mucin nanofiber or the complex in which mucin and mucin are crosslinked to obtain a dried mucin nanofiber or the complex in which mucin and mucin are crosslinked. The method for removing the aqueous solvent is not particularly limited, and for example, centrifugation, heat drying, freeze drying, spray drying, etc. can be used. For example, by using spray drying, the dried mucin nanofiber or the complex in which mucin and mucin are crosslinked can be obtained directly from the aqueous solvent.

[0070] In this production method, the timing of performing the crosslinking step is not particularly limited, but from the viewpoint of operability in electrospinning, it is preferably performed after the fiber formation step. For example, it is more preferable that the crosslinking step is performed between the fiber formation step described above and the washing step described below. With this configuration, it is possible to improve operability in electrospinning and to suitably produce mucin nanofibers with a high weight ratio of mucin.

[0071] [1-7] Cleaning process The present production method preferably includes a washing step in which the mucin nanofibers obtained in the fiber formation step are washed with an aqueous solvent. The washing step that the present production method may include can also be considered to be a step in which the water-soluble polymer in the mucin nanofibers is removed by washing (washing treatment) with an aqueous solvent. By including a washing step in the present production method, there is an advantage in that the water-soluble polymer in the mucin nanofibers can be removed, thereby increasing the mucin ratio in the mucin nanofibers.

[0072] Specific methods for washing mucin nanofibers include, for example, a method of adding an aqueous solvent to mucin nanofibers, a method of immersing mucin nanofibers in an aqueous solvent, a method of stirring mucin nanofibers while immersing them in an aqueous solvent, and the like, but are not limited to these.

[0073] The aqueous solvent used in the washing step is not particularly limited as long as it is an aqueous liquid that can wash the water-soluble polymer and does not alter the mucin nanofibers. Examples of the aqueous solvent include deionized water, tap water, distilled water, and saline. Among the aqueous solvents, deionized water, tap water, and distilled water are preferred because of their excellent washing effect.

[0074] The temperature of the aqueous solvent in the cleaning step is not particularly limited, and may be, for example, from room temperature (1° C. or higher and 40° C. or lower) to 100° C. In addition, aqueous solvent steam may be used as the aqueous solvent in the cleaning step. When an aqueous solvent or aqueous solvent steam at a high temperature of 60° C. or higher is used, a sterilizing effect can be expected in addition to a cleaning effect.

[0075] The amount of aqueous solvent used (total amount used) in the washing step is not particularly limited as long as it is capable of sufficiently washing the mucin nanofibers, but is, for example, at least 2,000 parts by mass, at least 10,000 parts by mass, or at least 100,000 parts by mass per 100 parts by mass of mucin nanofibers.

[0076] When the present production method includes a washing step, the washing step needs to be carried out at least once, but may be carried out multiple times.

[0077] In the present production method, the timing of carrying out the washing step is not particularly limited as long as it is carried out after the fiber-forming step. The washing step is preferably carried out, for example, following the fiber-forming step and the crosslinking step.

[0078] [1-8] Other processes (Dehydration process) The present production method may include a dehydration step of dehydrating the mucin nanofibers, preferably the mucin nanofibers after the washing step. The dehydration step can also be considered a step of dehydrating (dehydrating) the mucin nanofibers, thereby expelling water present inside the mucin nanofibers (e.g., water containing a water-soluble polymer) to the outside of the mucin nanofibers.

[0079] In the dehydration step, the method for dehydrating the mucin nanofibers is not particularly limited as long as it is a method capable of reducing the moisture content of the mucin nanofibers in a state in which they have absorbed liquid (for example, the aqueous solvent used for washing). Specific dehydration methods include, for example, a method in which the mucin nanofibers are left to stand at room temperature to dry naturally, a method in which the mucin nanofibers are brought into contact with various dehydrating liquids such as an aqueous solution containing a hydrophilic organic solvent, an aqueous solution with a low pH (for example, 3 or less), and an aqueous solution of a polyvalent metal salt (for example, calcium chloride), and a method in which a voltage is applied to the mucin nanofibers using a pair of electrodes. Methods for contacting the mucin nanofibers with the various dehydrating liquids include, but are not limited to, a method in which the liquid is added to the mucin nanofibers in a liquid-absorbed state, a method in which the mucin nanofibers in a liquid-absorbed state are immersed in the liquid, and a method in which the mucin nanofibers in a liquid-absorbed state are stirred while being immersed in the liquid.

[0080] When the mucin nanofibers are immersed in an aqueous solution containing a hydrophilic organic solvent in the dehydration process, the concentration of the hydrophilic organic solvent in the aqueous solution in which the mucin nanofibers are immersed is preferably 35% by mass or more, more preferably 40% by mass or more, and even more preferably 45% by mass or more.

[0081] In the dehydration process, when the mucin nanofibers are immersed in an aqueous solution with a low pH (e.g., 3 or less), the pH of the aqueous solution is preferably 3 or less, and more preferably 0.5 to 2.5. An aqueous solution containing an acid can be suitably used as the aqueous solution. As such an acid, either an inorganic acid or an organic acid can be used. In the case of an inorganic acid, for example, hydrochloric acid, sulfuric acid, etc. can be used. In the case of an organic acid, for example, tartaric acid, glycolic acid, malic acid, citric acid, succinic acid, acetic acid, etc. can be used. One of these acids may be used alone, or two or more of them may be mixed and used.

[0082] In the dehydration step, when the mucin nanofibers in a liquid-absorbed state are contacted with an aqueous solution of a polyvalent metal salt, examples of the polyvalent metal salt include salts of metals such as calcium, magnesium, aluminum, iron, cobalt, nickel, copper, etc., with chlorine, carbon, acetic acid, etc. One type of these polyvalent metal salts may be used alone, or two or more types may be used in combination.

[0083] When the present production method includes a dehydration step, the dehydration step may be performed at least once, but may be performed multiple times. When the present production method includes a washing step in addition to the dehydration step, the dehydration step is preferably performed after the washing step.

[0084] The present production method may include at least one of the above-mentioned washing step and dehydration step, or may include both the washing step and the dehydration step. In particular, since there is an advantage in that the water-soluble polymer present inside the mucin nanofiber in a liquid-absorbed state can be more effectively expelled from the mucin nanofiber, it is preferable that the present production method includes both the washing step and the dehydration step.

[0085] <2. Mucin nanofiber> The mucin nanofiber contains mucin and, optionally, a water-soluble polymer, in which the weight ratio of the mucin to the total weight of the mucin and the water-soluble polymer is greater than 50% by weight and less than 100% by weight, and the mucin nanofiber is substantially free of a water-insoluble polymer.

[0086] The mucin nanofibers contain mucin and, optionally, a water-soluble polymer. In this specification, the phrase "optionally containing a water-soluble polymer" means that the mucin nanofibers may or may not contain a water-soluble polymer.

[0087] In the present mucin nanofiber, the ratio of the weight of mucin to the total weight of mucin and water-soluble polymer is more than 50% by weight and not more than 100% by weight, preferably 60% by weight or more and 100% by weight or less, more preferably 70% by weight or more and 100% by weight or less, even more preferably 80% by weight or more and 100% by weight or less, and particularly preferably 90% by weight or more and 100% by weight or less.

[0088] The weight proportion of the water-insoluble polymer contained in the mucin nanofiber is 9 weight% or less, preferably 7 weight% or less, more preferably 5 weight% or less, more preferably 3 weight% or less, more preferably 1 weight% or less, and even more preferably 0 weight%, relative to 100 weight% of the mucin nanofiber.

[0089] In the present mucin nanofiber, the mucin is preferably crosslinked. With this configuration, it is possible to realize mucin nanofibers having increased strength and a high weight ratio of mucin.

[0090] In one embodiment of the present invention, the mucin nanofibers are produced by the present production method.

[0091] Furthermore, the mucin nanofiber may contain various components that are generated or not removed during the production process, so long as the effects of the present invention are achieved.

[0092] The average fiber diameter of the mucin nanofiber is not limited, and can be, for example, 1 nm or more and less than 1000 nm, 10 nm or more and less than 1000 nm, 100 nm or more and less than 1000 nm, 200 nm or more and less than 1000 nm, 300 nm or more and less than 1000 nm, 400 nm or more and less than 1000 nm, 500 nm or more and less than 1000 nm, 600 nm or more and less than 1000 nm, 700 nm or more and less than 1000 nm, or 800 nm or more and less than 1000 nm.

[0093] <3. Goods> An article comprising the mucin nanofibers of the present invention is also one embodiment of the present invention. In this specification, "an article comprising the mucin nanofibers of one embodiment of the present invention" may be referred to as "the article".

[0094] In the article, the mucin is preferably crosslinked.

[0095] This product can be used for various purposes, such as an in vitro evaluation device, a medicine, a quasi-drug, a cosmetic, a substrate, a collection material, a drug DDS device, a cryopreservation device, an adhesive, an eye patch, a bandage, or a napkin. EXAMPLES

[0096] The present invention will be described in more detail with reference to the following examples and comparative examples. However, the present invention is not limited to these examples. Examples obtained by appropriately combining the technical means disclosed in each example are also included in the scope of the present invention.

[0097] [A. Measurement of the average particle size of mucin molecule-derived particles and the zeta potential of the raw solution] The average particle size of particles derived from mucin molecules and the zeta potential of the raw solution were measured at different pH levels. If the mucin concentration is too high, the mucin solution will become viscous, making it difficult to measure the average particle size of particles derived from mucin molecules and the zeta potential of the raw solution. For this reason, measurements were performed using a mucin solution (0.1 w / v%) that was diluted to a level where it would not become viscous. The measurement method is described below.

[0098] 1. Preparation of Test Solutions 1-1. Purification of mucin Mucin (derived from pig stomach) powder (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added to purified water and stirred and dissolved at room temperature (1°C or higher and 40°C or lower) to obtain a mucin solution. The mucin solution was centrifuged to remove insoluble precipitates. The supernatant of the mucin solution from which the precipitates had been removed was dropped into methanol to precipitate mucin. The mucin precipitate was recovered by centrifugation and dried under reduced pressure. The residue after drying was used as purified mucin powder. Here, the mucin (derived from pig stomach) may be a mucin other than the above mucin (derived from pig stomach) (for example, the mucins listed in "(1-1) Mucin" above), and the results obtained in this case may be equivalent to those obtained when the above mucin (derived from pig stomach) is used.

[0099] 1-2. Preparation of purified mucin solution The purified mucin powder obtained in "1-1. Mucin purification" above was added to purified water and stirred and dissolved at room temperature to obtain a purified mucin solution (5 w / v%). Next, 1 mol / L hydrochloric acid and 1 mol / L aqueous sodium hydroxide solution were added to adjust the pH, and the solution was diluted with purified water to obtain a purified mucin solution (0.1 w / v%). The pH of the purified mucin solution (0.1 w / v%) diluted with purified water was measured. The results are shown in Table 1.

[0100] 2. Measurement of the average particle size of mucin molecule-derived particles and the zeta potential of the raw solution 2-1. Measurement of the average particle size of mucin molecule-derived particles 1 mL of the purified mucin solution (0.1 w / v%) prepared in "1-2. Preparation of purified mucin solution" above was added to a colorless, transparent disposable polyacrylic cell. This was attached to a particle size measuring device (Zetasizer Nano ZS, Malvern Instruments) and the particle size (Z-average, nm) of particles derived from mucin molecules was measured. The measurement conditions were a temperature of 25°C, a cell equilibration time of 60 seconds, and three measurements. The average value of the three measurements was used as the average particle size of particles derived from mucin molecules. The results are shown in Table 1 and Figure 1.

[0101] 2-2. Measurement of the zeta potential of the raw solution 1 mL of the purified mucin solution (0.1 w / v%) prepared in "1-2. Preparation of purified mucin solution" above was added to a disposable cell for zeta potential measurement (DTS1070, manufactured by Malvern Instruments, Inc.). This was attached to a zeta potential measuring device (Zetasizer Nano ZS, manufactured by Malvern Instruments, Inc.) and the zeta potential (mV) was measured. The measurement conditions were a temperature of 25°C, a cell equilibration time of 60 seconds, and three measurements. The average value of the three measurements was used as the zeta potential value of the raw material solution. The results are shown in Table 1 and Figure 1.

[0102] [Table 1]

[0103] 3.Results From Table 1 and Figure 1, it can be seen that mucin has an isoelectric point near pH 4.5, and the average particle size is maximum near the isoelectric point. As the zeta potential moves away from the isoelectric point, the average particle size becomes smaller, but when the zeta potential is negative, the average particle size is smaller than when it is positive.

[0104] B. Preparation and Observation of Mucin Nanofibers 4. Preparation of Test Solutions 4-1. Purification of mucin The same procedure as in "1-1. Mucin purification" above was carried out to obtain purified mucin powder.

[0105] 4-2. Preparation of purified mucin solution The purified mucin powder obtained in "4-1. Mucin purification" above was added to purified water and stirred and dissolved at room temperature to obtain a purified mucin solution (5 w / v%). The pH was adjusted by adding 1 mol / L hydrochloric acid and 1 mol / L sodium hydroxide aqueous solution (raw solution preparation process).

[0106] 4-3. Preparation of polyethylene oxide solution Polyethylene oxide (PEO) powder (Sigma-Aldrich Japan, LLC, average molecular weight: 2,000,000) was added to purified water and dissolved by stirring at room temperature to obtain a PEO solution (4 w / v%).

[0107] 4-4. Preparation of mucin / PEO raw material solution The purified mucin solution (5 w / v%) prepared in "4-2. Preparation of purified mucin solution" above and the PEO solution (4 w / v%) prepared in "4-3. Preparation of polyethylene oxide solution" above were mixed in equal volumes by volume to obtain a mucin / PEO raw material solution (final mucin concentration: 2.5 w / v%, final PEO concentration: 2 w / v%). The pH of the obtained mucin / PEO raw material solution was measured. The results are shown in Table 2. The pH of the mucin / PEO raw material solution was approximately the same as the pH of the mixed mucin solution (5 w / v%). The pH of the mucin / PEO raw material solutions in Examples 1 to 3 was equal to or higher than the isoelectric point of mucin (pH ≈ 4.5), and the pH of the mucin / PEO raw material solution in Comparative Example 1 was equal to or lower than the isoelectric point of mucin.

[0108] 5. Mucin Nanofiber Fabrication (Fiber formation process) The mucin / PEO raw material solution prepared in "4-4. Preparation of mucin / PEO mixed solution" above was attached to an electrospinning device (NANON, manufactured by MEC Co., Ltd.) and subjected to electrospinning to produce mucin nanofibers of Examples 1 to 3 and Comparative Example 1. The electrospinning conditions were a voltage of 25 kV, a flow rate of 1.0 mL / hour, a spinning width of 40 mm, and a spinning time of 60 minutes.

[0109] 6. Observation of mucin nanofibers The mucin nanofibers produced in "5. Production of mucin nanofibers" above were observed with a scanning electron microscope (JSM-6390FMM, JEOL Ltd.). The fiber diameter (fiber diameter) was measured using analysis software (ImageJ). The fiber diameters of 100 fibers were averaged and this was taken as the average fiber diameter (nm). The observation conditions were a magnification of 2,000x or 5,000x, an applied voltage of 10 kV, and a spot size of 50. An electron microscope image of the mucin nanofibers is shown in Figure 2.

[0110] 7. Calculation of mucin ratio in mucin nanofibers The mucin ratio (%) in the mucin nanofibers was calculated using the following formula (1). Mucin ratio (%) = C m / (C m +C p ) × 100 ···(1) C m : Mucin concentration in the mucin / PEO raw material solution (w / v%) C p : PEO concentration (w / v%) in the mucin / PEO raw material solution.

[0111] 8. Measurement of the average particle size of mucin molecule-derived particles and the zeta potential of the raw solution The same procedure as in "2. Measurement of the average particle size of mucin molecule-derived particles and the zeta potential of the raw solution" was carried out to measure the average particle size of mucin molecule-derived particles and the zeta potential of the raw solution of mucin solution (0.1 w / v%) adjusted to the same pH as the mucin / PEO raw solution. The results are shown in Table 2.

[0112] [Table 2]

[0113] 9.Results It was found from FIG. 2 that in Examples 1 to 3, no beads were formed on the fibers, but in Comparative Example 1, a large number of beads were formed on the fibers. [Industrial Applicability]

[0114] According to one embodiment of the present invention, it is possible to produce mucin nanofibers that have a high weight ratio of mucin, suppress the formation of beads, and improve operability during production. Therefore, one embodiment of the present invention can be suitably used for in vitro evaluation devices, medicines, quasi-drugs, cosmetics, substrates, collection materials, pharmaceutical DDS devices, cryopreservation devices, adhesives, eye patches, bandages, napkins, etc.

Claims

1. A method for producing mucin nanofibers, comprising a fiber formation step of electrospinning a raw material solution containing mucin and a water-soluble polymer, wherein the ratio of the weight of the mucin to the total weight of the mucin and the water-soluble polymer is greater than 50% by weight and the pH is equal to or higher than the isoelectric point of the mucin, to obtain mucin nanofibers.

2. The method for producing mucin nanofibers according to claim 1 , wherein the raw material solution has a negative zeta potential.

3. The method for producing mucin nanofibers according to claim 1, wherein the average particle diameter of particles derived from mucin molecules contained in the raw material solution is 300 nm or less.

4. The method for producing mucin nanofibers according to claim 1 , wherein the water-soluble polymer has at least one selected from the group consisting of a hydroxyl group, an amino group, a carboxyl group, and an ether bond.

5. The method for producing mucin nanofibers described in claim 1, wherein the water-soluble polymer is polyethylene oxide, polyvinyl alcohol, polyvinylpyrrolidone, polyethylene glycol, polyethyleneimine, polyacrylic acid, hydroxypropyl methylcellulose, methylcellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, polycarbophil, alginic acid, chitosan, β-glucan, gelatin, collagen, mixtures thereof, derivatives thereof, or copolymers thereof.

6. The method for producing mucin nanofibers described in claim 1, comprising at least one of a crosslinking process for crosslinking mucin contained in the mucin nanofibers obtained by the fiber formation process and / or crosslinking mucins contained in the raw material solution used in the fiber formation process, and a washing process for washing the mucin nanofibers obtained by the fiber formation process with an aqueous solvent.

7. A mucin nanofiber comprising mucin and, optionally, a water-soluble polymer, The weight ratio of the mucin to the total weight of the mucin and the water-soluble polymer is more than 50% by weight and 100% by weight or less; The mucin nanofiber has a water-insoluble polymer content of 9% by weight or less relative to 100% by weight of the mucin nanofiber.

8. The mucin nanofiber of claim 7, wherein the mucin is crosslinked and / or washed.

9. An article comprising the mucin nanofibers of claim 7 or 8.

10. The article according to claim 9 , wherein the article is an in vitro evaluation device, a medicine, a quasi-drug, a cosmetic, a substrate, a collection material, a drug DDS device, a cryopreservation device, an adhesive, an eye patch, a bandage, or a napkin.

Citation Information

Patent Citations

  • Jellyfish extract nanofibers

    WO2017179055A1